Institutions and Labor Market Outcomes in Sub-Saharan Africa - Fox, Louise; Oviedo, Ana Maria (World Bank, Washington, DC, 2012)
The authors use firm-level survey data from the manufacturing sector in 20 Sub-Saharan African countries to explore the links between labor market regulations and net job creation. A first look at firm characteristics, perceptions, and the dynamics of employment at the firm level suggests that labor regulations are not the main "binding constraint" on job creation. Other issues seem more important at this level of development. The analysis estimates the determinants of net job creation incorporating the legal origin of the country as a proxy for regulation. The findings show that, after controlling for other firm-level characteristics, legal origin is uncorrelated with net job creation in the short run.